The Evaluation of English Teachers’ Teaching Module of the New Merdeka Curriculum in Senior High School - Masrur Umar; Abdul Haris Sunubi; Saepudin; Zulfah Fakhruddin; Ambo Dalle (International Journal of Health, Economics, and Social Sciences (IJHESS), 2024)
This research evaluated the English Teacher's Modul Ajar in Merdeka Curriculum at the SMAN 1 Pamboang, by evaluating the implementation of the principles of essential, interesting, meaningful and challenging, relevant and contextual, and sustainable in its development. The qualitative evaluation of the English Modul Ajar on the Merdeka Curriculum involved document analysis and student interviews, which provided a detailed explanation of the implementation of the development principles for the five English teacher’s Modul Ajars. The results provide an in-depth understanding of the application of its development principles, as well as providing diverse perspectives from 52 students regarding the application of these principles in learning. Five English teachers' Modul Ajars, which include Compulsory English for Grades X, XI, and XII and Advanced English for Grades XI and XII, generally have implemented all the principles of Modul Ajar development, with some recommendations for improvement, according to the findings from document analysis. Students offered a variety of viewpoints on how the ideas of Modul Ajars development are applied in the classroom. The majority of pupils believed that English teachers applied concepts of developing principles to their teachings.